2008
DOI: 10.1093/alcalc/agm148
|View full text |Cite
|
Sign up to set email alerts
|

Review * The impact of alcopops on adolescent drinking: a literature review

Abstract: In place of beverage-specific interventions, a successful alcohol policy should look to implement evidence-based measures for the reduction of total alcohol consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 57 publications
2
38
0
1
Order By: Relevance
“…Conversely, several studies found that evidence of an association between alcopops consumption and higher risks of negative consequences in adolescents is scarce [11,28,29,[38][39][40][41]. The results of the present study confirm that these beverages are particularly appealing to young people as more than 60% of the students reported that they have drunk alcopops [9,11,42].…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Conversely, several studies found that evidence of an association between alcopops consumption and higher risks of negative consequences in adolescents is scarce [11,28,29,[38][39][40][41]. The results of the present study confirm that these beverages are particularly appealing to young people as more than 60% of the students reported that they have drunk alcopops [9,11,42].…”
Section: Discussionsupporting
confidence: 78%
“…Indeed, they are sweet beverages, often carbonated and/or fruitflavoured, that resemble soda or other soft drinks, and their pleasant taste tends to conceal the taste of alcohol [10,11,[28][29][30]. Accordingly, a significant rate of teenagers believe that alcopops contain less alcohol than beer [10,[31][32][33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These 'new drinks' had a trendy design and a sweet, non-alcoholic taste (Romanus, 2000;Lanier, Hayes, & Duffy, 2005), which may have enticed especially young children and girls, who would otherwise not drink, to embark on the use of alcohol (Metzner & Kraus, 2008). They were among the most popular alcoholic beverages among Dutch adolescents in secondary education in the 1990s (De Zwart et al, 2000;Ter Bogt, Van Dorsselaer, & Vollebergh, 2002).…”
Section: Societal Explanations For the Trendsmentioning
confidence: 99%